Does digital transformation enhance bank soundness? Evidence from Chinese commercial banks - Hu, Haifeng; Wei, Tao; Wang, Aiping (Journal of Financial Stability, 2025)
Compared with the previous literature on external FinTech, this paper is more interested in the role played by bank FinTech. On the basis of panel data from Chinese commercial banks spanning 2010–2021, this paper investigates the impact of digital transformation on bank soundness and its potential mechanisms. The empirical findings demonstrate a positive association between digital transformation and bank soundness, driven primarily by strategic and management digitization. Mechanistic analysis indicates that digital transformation improves bank soundness by mitigating risk-taking behavior and promoting diversification. The positive effect of digital transformation is more pronounced in state-owned and joint-stock banks, banks with higher liquidity mismatch and in the subsamples with greater levels of external FinTech development and economic policy uncertainty. Additional analysis suggests that digital transformation can still enhance bank soundness even in the presence of relatively lenient monetary and macroprudential policies, highlighting the harmonization and complementarity between internal innovation from digital transformation and external regulatory policies in maintaining banking stability. Overall, this paper contributes to the literature on bank FinTech, which focuses on the factors influencing bank stability. This study also provides a novel explanation for the relationship between financial innovation and financial stability.